Sponges of the Guyana Shelf - van Soest, Rob W.m. (Zootaxa, 2017)
Sponges collected on the Guyana Shelf, predominantly in Suriname offshore waters, by Dutch HMS ‘Snellius’ O.C.P.S. 1966, HMS ’Luymes’ O.C.P.S. II 1969, and HMS ‘Luymes’ Guyana Shelf 1970 expeditions are described in this study. Sponges were obtained by trawling, dredging or grabbing on sandy, muddy, shelly, and fossil reef bottoms at 88 stations between 19 and 681 m depth. A total of 351 samples were identified to species level, each consisting of one or more specimens of a given species from each individual station (together comprising 547 individuals and fragments). The collection yielded 119 species together belonging to all sponge classes, but in large majority are Demospongiae. All species are identified to species level, occasionally tentatively, and all are described and illustrated. A new subgenus is proposed, Tedania (Stylotedania) subgen. nov. and a previously synonymized genus, Tylosigma Topsent, 1894 is revived. Thirtysix species were found to be new to science, excluding the first Central West Atlantic record of the genus Halicnemia, not named at the species level because of lack of sufficient material. The new species erected are, in alphabetical order: Amphoriscus ancora sp. nov., Biemna rhabdotylostylota sp. nov., Callyspongia (Callyspongia) scutica sp. nov., Chelonaplysilla americana sp. nov., Cladocroce guyanensis sp. nov., Clathria (Axosuberites) riosae sp. nov., Clathria (Clathria) gomezae sp. nov., Clathria (Microciona) snelliusae sp. nov., Clathria (Thalysias) complanata sp. nov., Clathria (Thalysias) zeai sp. nov., Coelosphaera (Coelosphaera) lissodendoryxoides sp. nov., Craniella crustocorticata sp. nov., Diplastrella spirastrelloides sp. nov., Epipolasis tubulata sp. nov., Erylus rhabdocoronatus sp. nov., Erylus surinamensis sp. nov., Geodia pocillum sp. nov., Geodia sulcata sp. nov., Hemiasterella camelus sp. nov., Hymedesmia (Stylopus) alcoladoi sp. nov., Hymenancora cristoboi sp. nov., Penares sineastra sp. nov., Hymerhabdia kobluki sp. nov., Leucosolenia salpinx sp. nov., Petrosia (Strongylophora) devoogdae sp. nov., Placospongia ruetzleri sp. nov., Pyloderma tropicale sp. nov., Raspailia (Parasyringella) thamnopilosa sp. nov., Raspailia (Raspailia) johnhooperi sp. nov., Sphaerotylus bouryesnaultae sp. nov., Spirastrella erylicola sp. nov., Stelletta vervoorti sp. nov., Suberites crispolobatus sp. nov., Tedania (Stylotedania) folium subgen. nov. sp. nov., Timea tylasterina sp. nov., and Tylosigma ostreicola sp. nov. Two new combinations are proposed: Amphimedon nanaspiculata (Hartman, 1955) comb. nov. and Oceanapia ascidia (Schmidt, 1870) comb. nov. In addition, for two preoccupied combinations, new names, Coelosphaera (Coelosphaera) barbadensis nom. nov. and Hymedesmia (Hymedesmia) rowi nom. nov., are erected. The spatial distribution of the collected specimens over the Guyana Shelf was traced and the results were compared with existing information on bottom conditions. There was a convincing correlation between the location of fossil reefs and other hard substrates such as shell ridges with peaks in the occurrence of species diversity and specimen numbers. Stations made on sand and mud bottoms away from these zones of hard substrates were generally poor in species, but some were found to be rich in individuals of specialized soft bottom dwellers such as Tetilla pentatriaena, Tribrachium schmidtii, Fangophilina submersa, and Oceanapia species. The species composition of the Guyana Shelf was compared with that of neighbouring regions of the Caribbean and from North and East Brazil (Díaz in Miloslavich et al. 2010; Muricy et al. 2011). About 35% of the species encountered are widespread in the Central West Atlantic, occurring both to the north and to the south. Indications that the Guyana Shelf sponge fauna is clearly transitional are southernmost occurrences for Caribbean species (about 30%), and northernmost occurrences of Brazilian species (13%), with a high proportion (25%) of new species, which may be expected to have distributions extending to the Caribbean, to Brazil or both regions.